Vocational guidance: origin, evolution and current state - Di Doménico, María Cristina (2000)
The socio-professional sources of the vocational guidance are reviwed, in the world and in Latin America. It stands out that psychology, as science and as a profession, possesses vigorous links to this practice that, however, tends to its epistemic and praxic emancipation in some nations. The contemporary prob- lems of the guidance are presented in their economic, politics, cultural and pro-fessional dimensions.